World Tariff Liberalization in Agriculture: An Assessment Following a Global CGE Trade Model for EU15 Regions - Gabriele Standardi; Federico Perali; Luca Pieroni (Fondazione Eni Enrico Mattei (FEEM), 2014)
This paper aims at modeling a global CGE trade model for the EU15 subnational regions. This model is used to assess production reallocation across sectors in each EU15 region, assuming a scenario in which world tariff liberalization is implemented in the agricultural sector. The model is parsimonious in terms of data, focusing on unskilled and skilled labor as the source of heterogeneity across regions. A stylized model is built to interpret trade policy effects. Results show decreases in agricultural production in the EU15 of about 0.93%. All regions reduce agriculture but show different magnitudes in the relative changes of production. Large reallocation effects are observed between manufactures and services, some regions specializing in the former and others in the latter. In addition, the introduction of labor mobility within the EU15 and the EU27 causes strong amplification effects in manufactures and services.
Keywords: F13; D58; Q17; 330; CGE modeling; International trade; Agriculture